Guidelines for hazard evaluation procedures (CCPS, Center for Chemical Process Safety ; Wiley-Interscience, 2008)
Guidelines for Hazard Evaluation Procedures, 3rd Edition keeps process engineers updated on the effective methodologies that process safety demands. Almost 200 pages of worked examples are included to facilitate understanding. References for further reading, along with charts and diagrams that reflect the latest views and information, make this a completely accessible work. The revised and updated edition includes information not included in previous editions giving a comprehensive overview of this topic area.